Efficacy of Carboplatin and Isotretinoin in Children With High-risk Medulloblastoma: A Randomized Clinical Trial From the Children’s Oncology Group - Leary, Sarah E. S. (JAMA Oncol, 2021)
IMPORTANCE: Brain tumors are the leading cause of disease-related death in children. Medulloblastoma is the most common malignant embryonal brain tumor, and strategies to increase survival are needed. OBJECTIVE: To evaluate therapy intensification with carboplatin as a radiosensitizer and isotretinoin as a proapoptotic agent in children with high-risk medulloblastoma in a randomized clinical trial and, with a correlative biology study, facilitate planned subgroup analysis according to World Health Organization consensus molecular subgroups of medulloblastoma. DESIGN, SETTING, AND PARTICIPANTS: A randomized clinical phase 3 trial was conducted from March 2007 to September 2018. Analysis was completed in September 2020. Patients aged 3 to 21 years with newly diagnosed high-risk medulloblastoma from Children’s Oncology Group institutions within the US, Canada, Australia, and New Zealand were included. High-risk features included metastasis, residual disease, or diffuse anaplasia. INTERVENTIONS: Patients were randomized to receive 36-Gy craniospinal radiation therapy and weekly vincristine with or without daily carboplatin followed by 6 cycles of maintenance chemotherapy with cisplatin, cyclophosphamide, and vincristine with or without 12 cycles of isotretinoin during and following maintenance. MAIN OUTCOMES AND MEASURES: The primary clinical trial end point was event-free survival, using the log-rank test to compare arms. The primary biology study end point was molecular subgroup classification by DNA methylation array. RESULTS: Of 294 patients with medulloblastoma, 261 were evaluable after central radiologic and pathologic review; median age, 8.6 years (range, 3.3-21.2); 183 (70%) male; 189 (72%) with metastatic disease; 58 (22%) with diffuse anaplasia; and 14 (5%) with greater than 1.5-cm(2) residual disease. For all participants, the 5-year event-free survival was 62.9% (95% CI, 55.6%-70.2%) and overall survival was 73.4% (95% CI, 66.7%-80.1%). Isotretinoin randomization was closed early owing to futility. Five-year event-free survival was 66.4% (95% CI, 56.4%-76.4%) with carboplatin vs 59.2% (95% CI, 48.8%-69.6%) without carboplatin (P = .11), with the effect exclusively observed in group 3 subgroup patients: 73.2% (95% CI, 56.9%-89.5%) with carboplatin vs 53.7% (95% CI, 35.3%-72.1%) without (P = .047). Five-year overall survival differed by molecular subgroup (P = .006): WNT pathway activated, 100% (95% CI, 100%-100%); SHH pathway activated, 53.6% (95% CI, 33.0%-74.2%); group 3, 73.7% (95% CI, 61.9%-85.5%); and group 4, 76.9% (95% CI, 67.3%-86.5%). CONCLUSIONS AND RELEVANCE: In this randomized clinical trial, therapy intensification with carboplatin improved event-free survival by 19% at 5 years for children with high-risk group 3 medulloblastoma. These findings further support the value of an integrated clinical and molecular risk stratification for medulloblastoma. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT00392327